Acceptance of the Mobile Internet as Distribution Channel for Paid Content in Germany - Kaspar, Christian; Seidenfaden, Lutz; Ortelbach, Björn; Hagenhoff, Svenja (Business Web Strategy: Design, Alignment, and Application, Collection of selected IRMA 2006 papers, 2009)
This chapter is about a survey based on 7,178 valid responses which analyses the mobile content usage in Germany. Key findings are that paid mobile contents will not be a mass market in the medium term. Nevertheless, we found that respondents that are familiar with mobile radio and handset technology and read specialized printed media on a regular basis showed the highest acceptance of mobile paid contents. The mobile Internet is perceived as a chance for the media industry to generate additional revenues from paid contents. Successful business models for the mobile Internet will only be possible if mobile content formats generate added consumer value. In this context, media companies planning to establish mobile services for content distribution are facing the problem that acceptance of mobile services has not yet been researched thoroughly.<br
BUCHWISS::art-66